Immunological and molecular biomarkers in skin allergy therapy: monitoring inflammation, barrier function, and treatment response - Lisiecka, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2026)
This study explores the role of immunological and molecular monitoring in evaluating the efficacy of skin allergy therapies. The analysis focused on Th2-associated cytokines (IL-4, IL-5, IL-13), systemic markers (IgE, CD25), and chemokines (CCL17, CCL22, CCL26) as indicators of inflammatory activity. Structural proteins of the epidermal barrier (filaggrin, claudin-1, loricrin) and regulatory microRNAs (miRNA-155, miRNA-146a) were also assessed for their contribution to skin integrity and immune regulation. The findings demonstrated that elevated IL-4 and IL-13 levels, along with an imbalance between Th2 and Treg cells, correlated with disease severity. Successful therapy was associated with decreased cytokine levels, improved expression of barrier proteins, and modulation of microRNAs, indicating restored immune balance and reduced inflammation. These results highlight the value of integrated immunological and molecular monitoring for personalised assessment of therapy efficacy and the development of combined strategies targeting both immune dysfunction and barrier restoration.